Subsidizing strategies in a sustainable supply chain. Issue 2 (1st February 2018) - Fu, Jiangfeng; Chen, Xiangfeng; Hu, Qiying
Abstract: This paper inspects the effects of government subsidies on a supply chain that involves a supplier, a manufacturer, and consumers with electric vehicles (EVs). In practice, the government usually subsidizes different players (the supplier, the manufacturer, or consumers) in the supply chain using two subsidy schemes, namely the linear subsidy model (Model L) and the fixed subsidy model (Model F).We examine the equilibria of the EV supply chain that incorporates the influence from the government who is an external player in each subsidy model. To reach the target adoption of EVs, subsidizing the supplier / consumer presents the least costs to the government in Model L / Model F. We further compare all subsidizing policies in Model L / Model F to show that offering fixed subsidies to the consumer is the optimal subsidizing policy. We also conduct numerical experiments to show the robustness of the optimal subsidizing policy with varying demand uncertainty and target adoption. We extend the model to explore the effects of different subsidizing policies on consumer surplus and social welfare.